Thyroid Function in Preterm Infants during 5 Weeks of Life - Jashni Motlagh, Alireza; Boreiri, Saeideh; Rahimzadeh, Mitra (International Journal of Psychosocial Rehabilitation, 2020)
In preterm infants, delayed secretion of the thyroid-stimulating hormone hinders the diagnosis of congenital hypothyroidism. Therefore, this study was conducted to assess thyroid tests in preterm infants for five weeks to detect infants with congenital hypothyroidism manifesting with a delay for further treatment. This retrospective study was conducted in 186 preterm infants below 37 weeks’ gestation hospitalized in Imam Ali and Kamali hospitals in 2016-2017. Peripheral blood samples were collected from the infants 3-5 days, 2-3 weeks, and 5 weeks after delivery, and the results of TSH and T4 levels were available in their hospital records. The data were collected into data collection forms and analyzed using SPSS version 18. The TSH and T4 levels were compared between these three measurement times. The TSH level was significantly lower at 3-5 days of age compared to 3-5 weeks of age (p=0.016). Moreover, the serum level of TSH at 3-4 weeks of age showed a small decrease compared to 2-3 weeks of age, but no significant difference was observed in the TSH level between 3-4 and 4-5 weeks of age (p=0.82). Since thyroid function tests may be normal at birth, they can be used for disease diagnosis. Therefore, it is necessary to repeat thyroid and screening tests with a delay, and their parents should receive the proper training in this regard.